Submucosal endoscopy: the present and future - Zaheer Nabi; Duvvur Nageshwar Reddy (Korean Society of Gastrointestinal Endoscopy, 2023)
Submucosal endoscopy or third-space endoscopy utilizes the potential space between the mucosal and muscularis layers of the gastrointestinal tract to execute therapeutic interventions for various diseases. Over the last decade, endoscopic access to the submucosal space has revolutionized the field of therapeutic endoscopy. Submucosal endoscopy was originally used to perform endoscopic myotomy in patients with achalasia cardia, and its use has grown exponentially since. Currently, submucosal endoscopy is widely used to resect subepithelial tumors and to manage refractory gastroparesis and Zenker's diverticulum. While the utility of submucosal endoscopy has stood the test of time in esophageal motility disorders and subepithelial tumors, its durability remains to be established in conditions such as Zenker's diverticulum and refractory gastroparesis. Other emerging indications for submucosal endoscopy include esophageal epiphrenic diverticulum, Hirschsprung's disease, and esophageal strictures not amenable to conventional endoscopic treatment. The potential of submucosal endoscopy to provide easy and safe access to the mediastinum and peritoneal spaces may open doors to novel indications and rejuvenate the interest of endoscopists in natural orifice transluminal endoscopic surgery in the future. This review focuses on the current spectrum, recent updates, and future direction of submucosal endoscopy in the gastrointestinal tract.